Desarrollo eco-turístico - Díaz-Quesada, Andrea Carolina (Instituto Tecnológico de Costa Rica., 2017)
Costa Rica has approximately 4% of the earth’s biodiversity within its territory and is the main promoter of ecotourism in the world. Resulting in tourism acting as one of the main income factors for the economy of the country. Barbilla National Park is located in the Matina, Siquirres and Turrialba cantons, and it spans an area of 12.830 hectares. The park enclosures great natural diversity that currently is not being harnessed in the right way. A present threat in the form of agriculture and cattle raising, that is being used as a response to the lack of opportunity and employment by the local communities, is causing damage to the area’s natural resources. Being one of the poorest areas in the country and with high levels of social issues, the Matina region is looking for new ways to attract investments and opportunities throughout incentivizing the development of ecotourism in the region of the Barbilla National Park, a place that many times has been forgotten and is usually unknown by the local communities. It is from this situation that the idea for an Operative and Visitor Attention Center (OVAC) in the buffer area of the Barbilla National Park is born. The design project has the objective to increase job opportunities and catalyze the growth of the local economy through the development of sustainable tourism. The project is designed under the guidelines of ecotourism and sustainable architecture, with the focus on maximum preservation of existing natural areas. The outcome being an architectural design suitable to the site that respects the topography and climate of the region and the identity of local communities.
centro operativo y atención a visitantes en el área de amortiguamiento del Parque Nacional Barbilla en Punta de Lanza. Sector Matina
Proyecto de graduación (Licenciatura en Arquitectura y Urbanismo) Instituto Tecnológico de Costa Rica, 2017
Keywords: Parque Nacional Barbilla; Arquitectura sostenible; Ecoturismo